European survey and evaluation of sampling methods recommended by the standard EN ISO 18593 for the detection of Listeria monocytogenes and Pseudomonas fluorescens on industrial surfaces. Issue 7 (8th April 2020) - Brauge, Thomas; Barre, Lena; Leleu, Guylaine; André, Stéphane; Denis, Catherine; Hanin, Aurélie; Frémaux, Bastien; Guilbaud, Morgan; Herry, Jean-Marie; Oulahal, Nadia; Anger, Béatrice; Soumet, Christophe; et al.
ABSTRACT: The ready-to-eat products can be contaminated during processing by pathogen or spoilage bacteria, which persist in the industrial environment. Some bacterial species are able to form biofilms which protect them from environmental conditions. To check the bacterial contamination of the surfaces in the food industries, the professionals must regularly use surface sampling methods to detect the pathogen such as Listeria monocytogenes or the spoilage such as Pseudomonas fluorescens . In 2010, we designed and carried out a European survey to collect surface sampling information to detect or enumerate L. monocytogenes in food processing plants. A total of 137 questionnaires from 14 European Union Member States were returned. The outcome of this survey showed that the professionals preferred friction sampling methods with gauze pad, swab and sponges versus contact sampling methods. After this survey, we compared the effectiveness of these three friction sampling methods and the contact plates, as recommended in the standard EN ISO 18593 that was revised in 2018, on the recovery of L. monocytogenes and of P. fluorescens in mono-specie biofilms. This study showed no significant difference between the effectiveness of the four sampling methods to detach the viable and culturable bacterial population of theses mono-specie biofilms. Abstract : This article assesses for the first time the effectiveness of sampling methods recommended by the standard EN ISO 18593.